2001
DOI: 10.1002/lsm.1037
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the flash‐lamp pulsed‐dye laser treatment of facial port‐wine stains in childhood: A case of health care technology assessment

Abstract: The introduction and diffusion of the use of the FPDL in the treatment of PWS in childhood were uncontrolled, and the field was not prepared to use this technique properly. We believe that this nonadherence to the iterative HCTA model reflects the gradual way by which innovations find their way into clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…These methods can lead to the development of side effects such as scars and permanent depigmentation or. it is difficult to treat PWS without scarring [9][10][11]. So, laser therapy with pulsed dye laser (PDL) with epidermal cooling is a common treatment due to the low incidence of side effects.…”
Section: Introductionmentioning
confidence: 99%
“…These methods can lead to the development of side effects such as scars and permanent depigmentation or. it is difficult to treat PWS without scarring [9][10][11]. So, laser therapy with pulsed dye laser (PDL) with epidermal cooling is a common treatment due to the low incidence of side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Lasers have been used to treat PWS for over 30 years. 8 As demonstrated by its clinical efficacy, the pulsed dye laser (PDL) is the treatment of choice for PWS. 9 Shakespeare et al 10 evaluated the influence of laser treatment on quality of life (QoL) and found a significant improvement in mental health after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Lasers have been used in the treatment of PWS for more than 30 years. 7 The pulsed dye laser (PDL) is the treatment of choice as exhibited by its clinical efficacy. 8 It utilizes the principle of selective photothermolysis to injure the ectatic dermal capillaries, thereby reducing the redness and flattening the lesion.…”
Section: Introductionmentioning
confidence: 99%